Responsible agricultural investment: is there a significant role for the law to promote sustainability? - Nicolás Marcelo Perrone (Columbia University, Vale Columbia Center on Sustainable International Investment (VCC), 2011)
Today, the world food situation remains delicate. International investment and MNE involvement could be part of the solution to this problem. However, there are many concerns regarding the effects of these activities in host countries. An adequate interpretation of the Principles for Responsible Agricultural Investment could serve to promote sustainable foreign investment in agriculture.
Keywords: 330